Main Directions of Improving the Quality of Proffesional Tourism Education at the Current State of Russian Tourism Industry Development - BREL, Olga; ZAYTSEVA, Anna (Journal of Environmental Management and Tourism; Vol 10 No 6 (2019): JEMT Volume X Issue 6(38) Fall 2019DO - 10.14505//jemt.v10.6(38).16, 2019)
This paper identifies the main directions of improving the quality of training professional tourism personnel in the conditions of the development of the Russian economy and the modernization of professional education. The authors analyze the requirements of employers for potential employees, identify the main personnel problems affecting the quality of services in the tourism industry, consider the professional qualities necessary for successful employment in the field of tourism. The article presents the data of rating surveys of employers and students – future specialists in the field of tourism. The authors' conclusions and suggestions are based on the results of a number of sociological monitoring studies conducted in the Kemerovo region (Russia). The results obtained indicate the necessity to use different measure for improving the quality of professional tourism education.